2013
DOI: 10.7314/apjcp.2013.14.3.1813
|View full text |Cite
|
Sign up to set email alerts
|

Seroreactivity to Helicobacter pylori Antigens as a Risk Indicator of Gastric Cancer

Abstract: Background: Multiple etiologic factors are suspected to cause gastric cancer, the most important of which is infection with virulent types of Helicobacter pylori. Materials and Methods: We have compared 102 gastric cancer patients with 122 non-ulcer, non-cancer dyspeptic patients. Gastric specimens were evaluated for H. pylori infection by tissue-based detection methods. Patient sera underwent antigen-specific ELISA and western blotting using a Helicoblot 2.1 kit and antibody responses to various H. pylori ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…The prevalence of H. pylori infection was high among gastric cancer patients in many countries such as 91% in Singapore (Chau et al, 2002), 78% in Japan (Ono et al, 2012) and 100% in Iran (Karami et al, 2013). In this study, we demonstrated that overall H. pylori infection in gastric cancer was 83%.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The prevalence of H. pylori infection was high among gastric cancer patients in many countries such as 91% in Singapore (Chau et al, 2002), 78% in Japan (Ono et al, 2012) and 100% in Iran (Karami et al, 2013). In this study, we demonstrated that overall H. pylori infection in gastric cancer was 83%.…”
Section: Discussionsupporting
confidence: 54%
“…Since Warren and Marshall first isolated H. pylori and found its association with gastritis (Warren et al, 1983), many studies have suggested the relationship between H. pylori infection and gastric cancer (Parsonnet et al, 1991, Uemura et al, 2001, Demirel et al, 2013, Karami et al, 2013. In this study, the prevalence of active and non-active H. pylori infection in gastric cancer was 40% and 43% respectively.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Furthermore, those with H. pylori infection will get chance to develop gastric cancer between three to six times more than uninfected persons (Forman et al, 1991;Nomura et al, 1991;Parsonnet et al, 1991). Seroreactivity to the 89kDa (VacA) and 116kDa (CagA) proteins in H. pylori infected patients is risk indicators for cancer of stomach (Karami et al, 2013;Basiri et al, 2014). H. pylori eradication is not only significantly improve symptoms of FD patients (Moayyedi et al, 2006) but also decreases the gastric cancer incidence in asymptomatic infected Asian persons (Hamajima et al, 2004;Ford et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High risk individuals should be monitored for early signs of neoplastic changes and advised for possible life style changes (Karami et al, 2013). Some studies were conducted on the seroprevalence and risk factors of H. pylori infection from dyspeptic patients in Ethiopia (Desta et al, 2002;Asrat et al, 2004;Tadege et al, 2005;Moges et al, 2006).…”
Section: Prevalence and Risk Factors Of H Pylori From Dyspeptic Patimentioning
confidence: 99%